PERTANGGUNGJAWABAN PIDANA PEJABAT PEMBUAT AKTA TANAH DALAM PEMBUATAN AKTA JUAL BELI TANAH - Bisman Gaurifa (Jurnal Panah Hukum, 2022)
An authentic deed made by the PPAT is proof of ownership which can guarantee legal certainty if a dispute occurs one day. The existence of a PPAT in carrying out its duties and authorities in making deeds is required to act properly and correctly. Since the enactment of the Government Regulation (PP) which regulates land registration, the sale and purchase must also be carried out by the parties before the PPAT who is in charge of making the deed. By carrying out the sale and purchase before the PPAT, clear conditions are fulfilled (not dark legal actions, which are carried out in secret). The PPAT is responsible for examining the legal requirements for legal actions, and if there are irregularities in the implementation of the sale and purchase deed that are not in accordance with the procedure, the PPAT must be responsible for the documents drawn up. The type of research used is normative legal research using statutory law approaches, case approaches, and analytical approaches by collecting secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Qualitative data analysis, namely secondary data obtained from research results are arranged in a descriptive, logical and systematic manner. As well as drawing conclusions made using the deductive method. Based on the research findings and discussion, it can be concluded that criminal liability by the PPAT is legally regulated in Government Regulation Number 24 of 2016 concerning Officials for Making Land Deeds, strictly does not regulate criminal sanctions given to PPATs in making sales and purchase deeds and in Article 10 of the regulation said, that the responsibility of the PPAT profession only provides administrative sanctions. However, in the application of criminal responsibility to PPATs who are proven to have committed criminal acts while exercising their authority, PPATs can be charged using the Criminal Code which has been regulated starting from Article 263 of the Criminal Code to Article 266 of the Criminal Code and can be linked to Article 55 paragraph (1) of the Criminal Code, as well as suggestions from the author, namely that it is better to review this regulation by adding and formulating rules governing the penalty article against a PPAT who is proven to have committed a criminal act of issuing a sale and purchase deed that is not in accordance with the actual situation (falsification of a sale and purchase deed); as well as in making a sale and purchase deed, a PPAT is expected and required to be more careful and issue a sale and purchase deed without neglecting the standardization of the issuance of a sale and purchase deed